Involvement of hydroxyl radicals in neurogenic airway plasma exudation and bronchoconstriction in guinea-pigs in vivo. - Lei, Y. H. (1996)
1. Cigarette smoke induces plasma exudation in the airways of rodents by activation of capsaicin-sensitive 'sensory-efferent' nerves. The response is mediated predominantly by substance P (SP) and the magnitude of exudation is regulated by neutral endopeptidase (NEP). The component(s) of the smoke responsible for the activation of the nerves may be reactive oxygen radicals. We investigated the effect of the hydroxyl radical scavenger dimethylthiourea (DMTU), a regulator of superoxide anion, superoxide dismutase (SOD), and a regulator of hydrogen peroxide, catalase, on plasma exudation (measured using Evans blue dye) induced by cigarette smoke in guinea-pig main bronchi in vivo. The effect of DMTU on plasma exudation and non-cholinergic bronchoconstriction (measured as pulmonary insufflation pressure, PIP) induced by electrical stimulation of the vagus nerves was also assessed. Interaction between hydroxyl radicals and NEP was assessed with the NEP inhibitor phosphoramidon. 2. In each of the experiments, cigarette smoke increased plasma exudation by approximately 200% above air-exposed controls. Acute administration of DMTU (1.5 g kg-1, i.v. for 20 min) significantly reduced cigarette smoke-induced plasma exudation by 69%. In contrast, neither SOD (240,000 u kg-1, i.v.) nor catalase (400,000 u kg-1, i.v.) significantly affected the exudative response. 3. Chronic pretreatment with DMTU (1.25 g kg-1 over 4 days) significantly reduced bronchial plasma exudation induced by cigarette smoke by 72%. Phosphoramidon (1.5 mg kg-1, i.v.) completely reversed the inhibition by DMTU of cigarette smoke-induced plasma exudation. 4. Vagal stimulation increased plasma exudation by approximately 200% and PIP by approximately 250%. Acute treatment with DMTU had no significant inhibitory effect on these responses, whereas chronic pretreatment inhibited them by approximately 80%. Phosphoramidon reversed the inhibition by chronic DMTU. 5. SP (1 nmol kg-1) increased plasma exudation by approximately 250%, a response which was not inhibited by either acute or chronic DMTU. 6. We conclude that hydroxyl radicals, rather than superoxide anion or hydrogen peroxide, are involved in the induction of neurogenic plasma exudation and bronchoconstriction induced by cigarette smoke or by electrical stimulation of the vagus nerves. These radicals also affect the activity of NEP. Acute DMTU may affect directly the neural actions of hydroxyl radicals contained in the cigarette smoke. Chronic pretreatment with DMTU may inhibit the neurogenic airway responses by effects on tachykinin biosynthesis and/or axonal transport.